Excessive body weight of children and adolescents in the spotlight of their parents' overweight and obesity, physical activity, and screen time - Sigmund, Erik; Sigmundová, Dagmar; Badura, Petr (International journal of public health, 2020)
OBJECTIVES: The main aim of this study was to bridge the research gap in the countries of Central Europe using the family dyad approach to examine the associations of parents' overweight/obesity, physical activity (PA), and screen time (ST) with excessive body weight in their offspring. METHODS: The cross-sectional study included 1101 parent-child dyads (648/453 mother/father-child aged 4-16) selected by two-stage stratified random sampling with complete data on body weight categories, weekly PA (Yamax pedometer), ST (family logbook) collected over a regular school/working week during the spring and autumn seasons between 2013 and 2019. Binary logistic regression analyses were used to identify which of parents' lifestyle indicators were associated with the overweight/obesity of their offspring. RESULTS: The mother's overweight/obesity significantly increases her children's odds of overweight/obesity. Concerning fathers, active participation in organized leisure-time PA and reaching 10,000 steps per day significantly reduce the odds of overweight/obesity in their children and adolescent offspring. CONCLUSIONS: The cumulative effect of parental participation in organized leisure-time PA with their own family-related PA can be a natural means of preventing the development of overweight/obesity in their offspring.
Keywords: Weight Gain; Parents; Cross-Sectional Studies; vztahy mezi rodiči a dětmi; Family; Obesity; Europe; cvičení; mladiství; Evropa; Overweight/obesity; mužské pohlaví; Nuclear family triads; Step counts; průřezové studie; Adult; aktigrafie; čas strávený před obrazovkou; Overweight; hmotnostní přírůstek; dítě; Body Weight; Child; Child, Preschool; ženské pohlaví; Humans; předškolní dítě; Organized leisure-time physical activity; tělesná hmotnost; Parent–child dyads; Actigraphy; Screen Time; obezita; nadváha; Attitude to Health; postoj ke zdraví; Parent-Child Relations; Exercise; dospělí; Female; Adolescent; rodiče; lidé; Male